Bullying Victimization Among Junior High School Students in Aceh, Indonesia: Prevalence and its Differences in Gender, Grade, and Friendship Quality - Afriani, Afriani; Denisa, Denisa (Jurnal Ilmiah Peuradeun, 2021)
This study aimed to describe the prevalence of bullying victimization and its differences in gender, grade level, and friendship quality among junior high school students in Aceh, Indonesia. The study also investigated the moderation effect of gender on the association between friendship quality and bullying victimization. A total of 360 students from four schools in Banda Aceh was selected using Cluster and Disproportionate Stratified random sampling. The Revised Olweus Victim Questionnaire and Friendship Qualities Scale were used to obtain data on bullying victimization and friendship quality, respectively. The results indicated that 46.9 % of the students were reported being victimized by peers “2 or 3 times a month” or more often. Verbal was the most common form of victimization reported by students. Significant differences in bullying victimization were found concerning gender and friendship quality. The study revealed that males were more likely to report being victimized than females, while students who have a good relationship with their friends reported fewer experiences of victimization than others. Further, regression analysis indicated that gender significantly moderated the relationship between friendship quality and bullying victimization. Preventive interventions regarding peer relationships and gender may be useful in reducing bullying victimization in schools.